2020
DOI: 10.3390/vaccines8020291
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Experiences of Pregnant Women as a Predictor of the Intention to Become Vaccinated in Future Pregnancies in Spain

Abstract: A good perception of the vaccines administered during pregnancy favors immunization coverage, which is still not optimal for the influenza vaccine. To understand the predisposition towards vaccination in future pregnancies, a study was performed that evaluated the experiences of women with the vaccine or influenza. A cross-sectional study was conducted through telephone interviews given to a total of 683 postpartum women in two health departments from the Valencia Community (Spain). This interview asked about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
4
0
4
Order By: Relevance
“…A recent study conducted in Spain confirmed that women who usually adhere to influenza vaccination campaign are more prone to adhere to influenza vaccination during pregnancy [33,36].…”
Section: Discussionmentioning
confidence: 96%
“…A recent study conducted in Spain confirmed that women who usually adhere to influenza vaccination campaign are more prone to adhere to influenza vaccination during pregnancy [33,36].…”
Section: Discussionmentioning
confidence: 96%
“…El consejo vacunal realizado por la matrona es un predictor favorable de la inmunización de la mujer embarazada 19 y se asocia de forma significativa con el aumento de las tasas de cobertura 17 , 26 . La gestante y su pareja pueden ser mejor informados de los beneficios de la vacunación para la madre y el feto si las consultas son frecuentes, mensuales con las matronas, reforzando las recomendaciones de las autoridades sanitarias 27 , 28 .…”
Section: Discussionunclassified
“…Con todo lo citado y para superar el rechazo a las vacunas que se aconsejan durante el embarazo, gripe y tos ferina, es de vital importancia la recomendación realizada por un profesional sanitario 16 , 17 . En el trabajo de Rodríguez-Blanco et al 17 describieron algunos predictores favorables para la aceptación de la vacunación para la gripe, como fueron la experiencia con la enfermedad anteriormente y el conocimiento de los beneficios y la seguridad de la vacuna.…”
Section: Introductionunclassified
“…57,58 A desconfiança em relação à vacinação ocupa o segundo lugar em razões previstas para não querer se vacinar durante a gravidez. 59 Ponto forte citado no estudo com relação à aceitação e à confiança da vacina foi a percepção do risco do vírus e da doença, a confiança pública, a crença na importância de ter uma vacina COVID-19 e a eficácia da vacina durante a gravidez. 58 Em geral, as gestantes e lactantes relataram a segurança da vacina para criança e a para mãe como prioridades máximas em relação à vacina contra a COVID-19 e apresentaram maior nível de aceitação da vacina no terceiro trimestre de gestação, já que uma série de vacinas, incluindo as vacinas influenza (H1N1) e dTpa, é, particularmente, recomendada durante o terceiro trimestre.…”
Section: /19unclassified
“…31,34,36,38 Logo, é importante que os profissionais de saúde aproveitem as experiências de vacinações em ocasiões anteriores e a percepção que as mulheres têm sobre as vacinas para fornecer conselhos eficientes para aumentar a cobertura vacinal durante a gravidez. 59 Os profissionais de saúde têm atuação relevante na assistência de pré-natal como provedores de informações e incentivos à vacinação com impacto na adesão das mulheres às vacinas no período gravídico-puerperal. 7 O apoio e o fornecimento de informações sobre a vacinação pelos profissionais de saúde é uma ótima oportunidade para alcançar um histórico vacinal completo da mulher.…”
Section: /19unclassified